Strengthening the Role of Higher Education in Reducing Stunting Prevention in North Sumatra - Ismail Efendy; Asriwati Amirah; Mappeaty Nyorong; Sri Maryani Tanjung; Soeandi Malik Pratama (Journal of Universal Community Empowerment Provision, 2023)
Indonesia has established specific objectives aligned with the Sustainable Development Goals (SDGs) Program for the year 2030 in the domain of public health. These objectives primarily focus on enhancing nutritional standards and overall health quality as a means of addressing the prevailing issue of stunting. The attainment of the Sustainable Development Goals (SDGs) necessitates proactive preparation and effective coordination across various sectors. In the past two decades, progress in addressing the issue of stunting has been notably sluggish. On a global scale, there has been a mere 0.6% annual reduction in the prevalence of stunted growth among children since 1999. According to projections, if the current trend persists, it is anticipated that in 15 years, approximately 450 million children will be affected by growth retardation or stunting. It is hypothesized that the lack of cross-sectoral roles in preventing stunting is the causative factor. Therefore, it is imperative to enhance the role through convergence actions in order to expedite the reduction of stunting. The role of higher education involves implementing a mentoring strategy for both educators and engaging students in the Program to Accelerate the Reduction of Stunting at 10 locations in the Labuhan Batu district. This program adopts a five-pillar approach, which includes: (1) enhancing the commitment and leadership of the Village/Kelurahan Government, (2) strengthening and developing systems, data, information, research, and innovation, (3) promoting behavior change and community empowerment in terms of nutrition, healthy behavior, cooperation, and self-reliance, (4) implementing specific and sensitive interventions through a stunting caring family approach, and (5) ensuring food security at the individual, family, and community levels by optimizing the utilization of local food ingredients. The factors that promote the implementation of convergence initiatives to expedite the reduction of stunting encompass the government's dedication, alongside the engagement of diverse stakeholders from both the healthcare and non-healthcare domains.